Inflammatory models of depression in rodents and humans - Markov, Dmitrii D.; Zozulya, Svetlana A.; Dolotov, Oleg V. (Frontiers in Psychiatry, 2026)
The precise pathophysiological mechanisms underlying major depressive disorder (MDD) remain poorly understood. Substantial evidence implicates immune-mediated mechanisms in the pathogenesis of this clinically heterogeneous and multifactorial disease. This review provides a comprehensive synthesis of current knowledge regarding the association between inflammation and depression, critically evaluates established approaches for modeling inflammation-induced depressive states in both rodents and humans, and assesses these models against standard validity criteria. The empirical link between depression and immune dysregulation is supported by several key lines of evidence: elevated circulating cytokine levels in MDD patients, the induction of depressive symptoms during therapeutic administration of pro-inflammatory cytokines, the significant comorbidity of MDD with chronic inflammatory diseases, the anti-inflammatory properties of conventional antidepressants and the alleviation of depressive symptoms during anti-inflammatory therapy. Various immune activators are employed to model inflammation-associated depression. Experimental human models primarily utilize lipopolysaccharide (LPS) administration or typhoid vaccination. Corresponding rodent models employ LPS, direct administration of pro-inflammatory cytokines, or immunization with BCG vaccine. In rodent models, the administration of classical antidepressants effectively attenuates the severity of depressive-like behaviors induced by LPS. The predictive validity of the LPS-induced depression model is further corroborated by the demonstrated antidepressant-like efficacy of the rapid-acting agent ketamine. Data on the effects of antidepressants within controlled experimental inflammatory models in humans remain scarce and the impact of novel rapid-acting agents like ketamine and psychedelics in this context remains entirely unexplored. Human experimental studies demonstrate high consistency and reproducibility regarding LPS dosing, experimental timelines, and symptom assessment. Conversely, rodent studies exhibit significant heterogeneity across these same parameters. A major limitation shared by most existing inflammatory models, in both humans and rodents, is their non-chronic nature and the development of tolerance with repeated inducer administration. A critical translational challenge lies in establishing the homology between behavioral outcomes in rodents and the clinical symptomatology of human depression. The development of refined inflammatory models of depression that more rigorously satisfy established validity criteria is imperative. Such models are crucial for elucidating the underlying pathophysiological mechanisms of the disorder and for facilitating the discovery of novel, effective pharmacotherapies.